Study of different fillers on aluminium alloys 6061 and 7075 by MIG welding - Nur Fakhriah, Mohd Noordin (2020)
Weight reduction in automotive and aircraft industries is a main concern in improving fuel economy and reducing environmental pollutions. Recently, dissimilar joint of aluminum alloys are constantly gaining importance as lightweight structural materials for automotive applications. AA6061 and AA7075 are widely used in automobile and aviation industry due to its light weight, high corrosion resistance, stronger and high hardness. Metal Inert Gas (MIG) welding method was used due to its low cost and it is general methods used by the welders Nevertheless, welding dissimilar metal can generate defects, such as porosity, crack and many others which could limit its development. These defects may result degradation of mechanical properties of the joint such as tensile strength and hardness which especially occurred at heat affected zone (HAZ). One of the major causes associated with the dissimilar welding of aluminium alloys is the difference in composition in the alloying element which attribute to different thermal conductivity of the materials. These problems can be encountered with proper selection of parameters such as welding current (WC), welding voltage (WV), welding speed (WS) and filler metal. This research is focuses on the weldability between dissimilar AA6061 and AA7075 by MIG welding method and to investigate the effect of different filler metal on the mechanical and microstructural properties of MIG welded dissimilar AA6061 and AA7075. AA6061 and AA7075 thickness of 2 mm were welded by using semi-automated MIG welding machine. The highest UTS with the combination of WC, WV and WS for joining by using ER5554 is 95 A, 18 V and 3 mm/s, for joining by using ER5183 is 100 A, 17 V and 3 mm/s and joining by using ER5356 is 115 A, 18 V and 4 mm/s was produced. Visual observation of minimal defect was observed. Specimen with highest UTS which is 168.67 MPa, 234.93 MPa and 261.23 MPa for each joining by using filler metal ER5554, ER5183 and ER 5356, respectively were evaluated for mechanical properties. The hardness value at fusion zone (FZ) region for joint using ER5356 filler exhibited the highest value which is 123 Hv compared than joint using filler ER5183 and filler ER5554 with 109 Hv and 93.7 Hv, respectively. The average hardness values of HAZ region are lower than the BM and FZ for both sides. For side AA6061, the average hardness values of HAZ were approximately similar which are 75.3 Hv, 78.4 Hv and 79.3 Hv for joint with filler ER5554, ER5183 and ER5356, respectively. Meanwhile, HAZ region for side AA7075 the hardness value at joint using filler ER5183 and ER5356 exhibited same value which is 121 Hv and using filler ER5554 is 71.6 Hv. HAZ region was lower than the other region is due to the changes of the grain size due to the heat from the welding process that changes the microstructure of base metal (BM). From the result of grain size obtained, at HAZ side AA6061 by using filler ER5356 shows the finer size which is 73.71 μm for joining using ER5183 and ER5554 coarser size with value of 75.38 μm and 75.5 μm, respectively. HAZ side AA7075 also shows the same pattern which is has finer grain size by using filler ER5356 with value of 79.65 μm. HAZ side AA7075 by using filler ER5183 and ER5554 shows a coarser size with value of 83.3 μm and 89.6 μm, respectively. In conclusion, the aluminum alloy AA6061 and AA7075 was successfully welded by using Metal Inert Gas. Different filler metal gives effect to the mechanical and microstructural properties of the joint. The joining by using filler with higher Mg content shows higher tensile strength with fine and equiaxed grain size that indicate higher hardness.